Lung extralobal pulmonary sequestral combined with pulmonary tuberculosis: Case report - Santos Cavalcanti Melo, Maria Cecília (2018)
The combination of pulmonary sequestration, tuberculosis and primary immunodeficiency is a rare condition, with few cases described in the literature. The purpose is to report a case of a female child with extralobar pulmonary sequestration, primary immunodeficiency and association with pulmonary tuberculosis. Case report: ALLV, two year-old, female, was born by cesarean section, with gestational age of 39 weeks, with low an rectal agenesis and ventricular septal defect. She evolved with asthma bronchiolitis and three episodes of pneumonia, resistant to conventional treatments. After vaccination with BCG she developed BCGite, which was treated with isoniazid for 6 months. In the last episode of pneumonia considered as nonspecific she evolved without adequate response to the therapeutics scheme. She underwent a therapeutic test for pulmonary tuberculosis. She received medical investigation, which detected congenital malformations of the tracheobronchial tree, such as right tracheal bronchus and left extralobar pulmonary sequestration and left middle lobesyndrome with bronchial fistula, highly suggestive of tuberculosis. She was kept on medication for tuberculosis with progressive improvement of general condition and growth and adequate developments. Comments: The association of pulmonary sequestration, immunodeficiency and tuberculosis is rare. Occasionally the dysplastic lung mass (pulmonary sequestration) may be the site of multiple pyogenic infection and rarely tuberculosis, as it happens in the reported case. The precedence of the tuberculosis treatment is necessary so that, after infection control, therapeutic approaches to the various malformations will bedecided. In the future, these anomalies may cause complications that can put the patient's life at risk.